Weak Forms of L (θ-Generalized Closed) - Spaces الاصدار: - Mohammed, Arkan J (Al-Nahrain Journal of Science, 2012)
In this paper, we introduce some concepts namely θ-generalized Li-spaces, where i=1,2,3,4, which are weaker forms of L(θ-generalized closed)-spaces, these are spaces whose Lindelof subsets are θ-generalized closed and study some of their properties and investigate their relationships with L(θ-generalized closed)- spaces as well as among themselves